FRENCH POLITICAL THOUGHT ABOUT THE CRISIS OF THE MODERN MODEL OF EUROINTEGRATION - A. A. Vershinin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2017)
The primary focus of the paper is on the contemporary sociopolitical discussion in France about the problems of European integration. One of its key aspects, the debate among the eminent thinkers, philosophers and historians, is analyzed. The French intellectuals always emphasized the problem of the united Europe building considering the continent as the field for the France’s economic, political and cultural expansion. Since the second half of the XXth century the vision of the country’s future has been inherent in the European project’s realization. From the French thinkers’ point of view the European community turned into a kind of superstructure over the liberal democratic states that neutralized the risks of their interaction as well as opened the prospects for mutual development. At the same times these institutes were a sort of temporary construction. The French commentators point out that from the very beginning they had no the firm political foundation. This preconditioned the current crisis. The problem of the legitimacy of the European institutions turned out to be insoluble. The idea to construct them beyond the field of the common nationhood on the ground of latent economic integration removed the possibility to create a kind of superstate in the form of federation. The post-statist model based on the idea of European civil society remained nothing but the abstraction. The mechanisms of the redistribution that could help creating the united social field are absent. The choice in favor of the so called value legitimacy was made that to the French thinkers’ mind produced an illusion that the European institutions can be stabilized. In fact this laid the groundwork for their deconstruction in the future. The most of the French intellectuals are united in the pessimism as of the EU’s prospects. Their evaluations of the latest signs of the crisis only vary in what concerns the point of view on the problem.The eurooptimists remain in minority while the eurosceptics are debating the measures that should be taken in order to reconstruct the EU. Some of them come to conclusion that this question should be regarded as part of the reforming of the contemporary liberal democratic state as such.